Solvent-free synthesis of NiCo2S4 having the metallic nature - Ahmed, Sardar; Ahmad, Mushtaq; Yousaf, Muhammad Hasnain; Haider, Sumain; Imran, Zahid; Batool, S. S.; Ahmad, Ishaq; Shahzad, Muhammad Imran; Azeem, Muhammad (Frontiers in Chemistry, 2022)
Nickel-cobalt sulfide (NiCo2S4) is a prominent member of bimetallic transition metal sulfides. It is being widely used for a variety of applications such as electrode material, photocatalysis, and energy storage devices (like pseudo capacitors, supercapacitors, solar cells, and fuel cells) due to its better electronic conductivity, manageable morphology, and high capacitance. This work presents the one-step solventless synthesis of NiCo2S4 sheet-like nanostructures for the first time and we then explore their metallic nature. Scanning electron microscopy (SEM) and transmission electron microscopic (TEM) analysis show the sheet-like grown morphology. Few nanorods are also seen. Except for a recent study (Xia et al. 2015) that shows metallic behavior, most of the reports show that NiCo2S4 is a semiconductor with claimed bandgap between 1.21-2.4 eV. In this study, we observe from UV-Vis and diffuse reflectance spectroscopy (DRS) that NiCo2S4 has a specific band gap value between 2.02-2.17 eV. However, IV characteristics in the temperature range of 300 K to 400 K show that NiCo2S4 is a metal with a positive temperature coefficient of resistance consistent with a recent report. Furthermore, we see the ohmic conduction mechanism. The Arrhenius plot is drawn, and the activation energy is calculated to be 3.45 meV. The metallic nature is attributed to the coupling of two metal species (nickel and cobalt), which accounts for its superior conductivity and performance in a variety of essential applications.